2023
DOI: 10.3390/v15051162
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Heterologous and Homologous COVID-19 Vaccination: A Longitudinal Study of Antibody Decay

Abstract: The humoral response after vaccination was evaluated in 1248 individuals who received different COVID-19 vaccine schedules. The study compared subjects primed with adenoviral ChAdOx1-S (ChAd) and boosted with BNT162b2 (BNT) mRNA vaccines (ChAd/BNT) to homologous dosing with BNT/BNT or ChAd/ChAd vaccines. Serum samples were collected at two, four and six months after vaccination, and anti-Spike IgG responses were determined. The heterologous vaccination induced a more robust immune response than the two homolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…All three vaccines showed high efficacy in preventing severe disease courses ( 3 5 ) and were also shown to mitigate the risk of long-term manifestation of COVID-19 ( 6 , 7 ). We and others could show in head-to-head comparisons that homologous and heterologous use of mRNA vaccines resulted in a significantly stronger humoral immune response and that was true after two ( 8 11 ) and also after three doses of vaccine ( 12 15 ). In contrast, results for T cell memories were not as clear cut with some descriptions of mRNA vaccines being superior to the homologous vector regimen ( 16 18 ), while others published comparable results for both vaccines ( 9 , 10 , 19 , 20 ).…”
Section: Introductionmentioning
confidence: 77%
“…All three vaccines showed high efficacy in preventing severe disease courses ( 3 5 ) and were also shown to mitigate the risk of long-term manifestation of COVID-19 ( 6 , 7 ). We and others could show in head-to-head comparisons that homologous and heterologous use of mRNA vaccines resulted in a significantly stronger humoral immune response and that was true after two ( 8 11 ) and also after three doses of vaccine ( 12 15 ). In contrast, results for T cell memories were not as clear cut with some descriptions of mRNA vaccines being superior to the homologous vector regimen ( 16 18 ), while others published comparable results for both vaccines ( 9 , 10 , 19 , 20 ).…”
Section: Introductionmentioning
confidence: 77%
“…Additionally, previous research has shown that those receiving heterologous vaccination compared with those receiving homologous vaccination had slower waning of antibodies [29]. As vaccine scheduling in regard to both dosing and vaccine product administered differed between countries [30], this might also explain why some studies reported an increase in AE after the second and third dose.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody levels prior to a vaccination are influenced by the interval between previously administered vaccines or infection and vaccination, with longer dosing intervals between vaccinations possibly leading to higher antibody responses [ 28 ]. Additionally, previous research has shown that those receiving heterologous vaccination compared with those receiving homologous vaccination had slower waning of antibodies [ 29 ]. As vaccine scheduling in regard to both dosing and vaccine product administered differed between countries [ 30 ], this might also explain why some studies reported an increase in AE after the second and third dose.…”
Section: Discussionmentioning
confidence: 99%